Reporting Guidelines for Health Care Simulation Research: Extensions to the CONSORT and STROBE Statements. Issue 4 (August 2016) - Cheng, Adam; Kessler, David; Mackinnon, Ralph; Chang, Todd P.; Nadkarni, Vinay M.; Hunt, Elizabeth A.; Duval-Arnould, Jordan; Lin, Yiqun; Cook, David A.; Pusic, Martin; Hui, Joshua; Moher, David; et al.
Abstract : Introduction: Simulation-based research (SBR) is rapidly expanding but the quality of reporting needs improvement. For a reader to critically assess a study, the elements of the study need to be clearly reported. Our objective was to develop reporting guidelines for SBR by creating extensions to the Consolidated Standards of Reporting Trials (CONSORT) and Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) Statements. Methods: An iterative multistep consensus-building process was used on the basis of the recommended steps for developing reporting guidelines. The consensus process involved the following: (1) developing a steering committee, (2) defining the scope of the reporting guidelines, (3) identifying a consensus panel, (4) generating a list of items for discussion via online premeeting survey, (5) conducting a consensus meeting, and (6) drafting reporting guidelines with an explanation and elaboration document. Results: The following 11 extensions were recommended for CONSORT: item 1 (title/abstract), item 2 (background), item 5 (interventions), item 6 (outcomes), item 11 (blinding), item 12 (statistical methods), item 15 (baseline data), item 17 (outcomes/estimation), item 20 (limitations), item 21 (generalizability), and item 25 (funding). The following 10 extensions were recommended for STROBE: item 1 (title/abstract), item 2 (background/rationale), item 7 (variables), item 8 (data sources/measurement), item 12 (statistical methods), item 14 (descriptive data), item 16 (main results), item 19 (limitations), item 21 (generalizability), and item 22 (funding). An elaboration document was created to provide examples and explanation for each extension. Conclusions: We have developed extensions for the CONSORT and STROBE Statements that can help improve the quality of reporting for SBR. Abstract : Supplemental digital content is available in the text.